2005
DOI: 10.1037/0012-1649.41.1.75
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Gendered Vocabulary and Communicative Action in Young Children.

Abstract: Development of children's vocabularies for gender-typed words and communicative actions was investigated longitudinally from 13 to 36 months and in a group of 9.5-month-olds. Vocabularies of gendered words were assessed using lists of adult-rated gender-typed words from the MacArthur-Bates Communicative Development Inventories (CDI; L. Fenson et al., 1994). At 24 to 36 months, girls' and boys' productive vocabularies contained more same-gender-typed words than other-gender-typed words. Receptive vocabulary gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
(43 reference statements)
1
22
0
4
Order By: Relevance
“…Studies have identified gender-related differences between the vocabularies of boys and girls. Stennes, Burch, Sen, and Bauer (2005), for example, did a measure of the vocabulary of children from 9 to 36 months of age and found that by 30 months of age, gender-typed vocabulary was relatively stable. A vocabulary list consisting of words that had been rated as being feminine or masculine by an adult sample was used to help determine these findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have identified gender-related differences between the vocabularies of boys and girls. Stennes, Burch, Sen, and Bauer (2005), for example, did a measure of the vocabulary of children from 9 to 36 months of age and found that by 30 months of age, gender-typed vocabulary was relatively stable. A vocabulary list consisting of words that had been rated as being feminine or masculine by an adult sample was used to help determine these findings.…”
Section: Discussionmentioning
confidence: 97%
“…Although it is clear that the pictures in the BNT mainly consist of artefacts, it is not obvious which of those objects may apply more to girls than boys or vice versa. One approach may be to apply the method used by Stennes et al (2005) to BNT analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by the quality of stimulation. Mothers with higher levels of education tend to provide different types of daily stimulation, more play materials and appropriate games, along with better physical and temporal space management and better emotional involvement [51]. Higher levels of education are also associated with a more complex speech [21], allowing mothers to talk more with their children using a richer vocabulary [17].…”
Section: Discussionmentioning
confidence: 98%
“…Stennes et al (2005) found that 2-3 year-olds produced more same-versus opposite-gender words. However, these words mainly denoted female or male beings (e.g., aunt, uncle).…”
Section: Introductionmentioning
confidence: 96%